Campylobacter colonization and undernutrition in infants in rural eastern Ethiopia — a longitudinal community-based birth cohort study - Chen, Dehao; McKune, Sarah Lindley; Yang, Yang; Usmane, Ibsa Aliyi; Ahmed, Ibsa Abdusemed; Amin, Jafer Kedir; Ibrahim, Abdulmuen Mohammed; Seran, Abadir Jemal; Shaik, Nurmohammad; Ojeda, Amanda; Hassen, Bahar Mummed; Deblais, Loic; et al. (Frontiers in Public Health, 2025)
BackgroundCampylobacter is associated with environmental enteric dysfunction (EED) and malnutrition in children. Campylobacter infection could be a linchpin between livestock fecal exposure and health outcomes in low-resource smallholder settings.MethodsWe followed a birth cohort of 106 infants in rural smallholder households in eastern Ethiopia up to 13 months of age. We measured anthropometry, surveyed sociodemographic determinants, and collected stool and urine samples. A short survey was conducted during monthly visits, infant stool samples were collected, and Campylobacter spp. was quantified using genus-specific qPCR. In month 13, we collected stool and urine samples to assay for EED biomarkers. We employed regression analyses to assess the associations of household determinants with Campylobacter colonization, EED, and growth faltering.ResultsThe Campylobacter load in infant stools increased with age. The mean length-for-age Z-score (LAZ) decreased from −0.45 at 3–4 months of age to −2.06 at 13 months, while the prevalence of stunting increased from 3 to 51%. The prevalence of EED at 13 months of age was 56%. A higher Campylobacter load was associated with more frequent diarrhea. Prelacteal feeding significantly increased Campylobacter load in the first month of life. Over the whole follow-up period, Campylobacter load was increased by keeping chickens unconfined at home and unsanitary disposal of infant stools while decreased by mothers’ handwashing with soap. Longitudinally, Campylobacter load was positively associated with food insecurity, introduction of complementary foods, and raw milk consumption. There were no significant associations between Campylobacter load, EED, and LAZ.ConclusionThis study found that most determinants associated with increased Campylobacter infection were related to suboptimal feeding practices and hygiene. The findings related to livestock-associated risks were inconclusive. Although stunting, EED, and Campylobacter prevalence rates all increased to high levels by the end of the first year of life, no significant association between them was identified. While additional research is needed to investigate whether findings from this study are replicable in other populations, community efforts to improve infant and young child feeding practices and food hygiene, and water, sanitation, and hygiene (WaSH) at the household level, could reduce (cross-)contamination at the point of exposure.